Estudo da resistência ao desgaste e corrosão do aço AISI 4340 com tratamento a plasma de nitrocementação, revestimento DLC e multicamada (nitrocementação + DLC) - Campos, Lucas de Almeida Pires de (2020)
Duplex treatments are performed seeking out to promote additional tribological property for a material, for example, diamond-like carbon (DLC) films deposited on AISI 4340 steel nitrocarburizing surfaces. DLC films have properties such as high hardness, chemical inertness and low coefficient of friction, but may exhibit defects in their formation that affect the corrosion resistance of the material. Plasma nitrocarburizing treatments produce controlled thickness layers with high corrosion resistance. The aim of this work is to study the wear and corrosion properties of AISI 4340 steel after plasma nitrocarburizing, DLC film deposition and duplex treatments (nitrocarburizing + DLC films). The Nitrocarburizing treatments by plasma were performed with 80% N2 + 17% H2 + 3% CH4 at 400, 450, 500, 525 and 550°C for 5 hours. The deposition of DLC film was performed by DC-PECVD method using 90% CH4 + 10% Ar at 200°C for 2 hours with a silicon interlayer to improve DLC adhesion to the surface metal. The duplex treatment was performed with the best temperature of the nitrocarburizing formed followed by DLC film deposition with silicon interlayer. Micro-abrasive wear tests by fixed ball and corrosion tests by cyclic polarization showed that all material treated presented increase of wear and corrosion resistance when compared untreated material, but the duplex treatment material provided lower wear volume and induced more positive corrosion potential than individually treated materials, showing that the duplex treatment can improve even more the properties in wear and corrosion of the AISI 4340 steel.